VD_FINDINFO HC / 2013 / 522 vom 20. August 2013 - VD Tribunal cantonal (2013)
DOMICILE, VISITE, PROTECTION DE L'UNION CONJUGALE, MENACEEN GÉNÉRAL | 176 al. 1 ch. 2 CC, 176 al. 3 CC, 176 CC, 292 CP, 312 al. 1 CPC (CH)